How Is Learning Motivation Shaped Under Different Contexts: An Ethnographic Study in the Changes of Adult Learner’s Motivational Beliefs and Behaviors Within a Foreign Language Course - Bo, Wenjin Vikki; Fu, Mingchen (Frontiers in Psychology, 2018)
There has been a burgeoning interest of students’ motivational beliefs in determining their motivational behaviours in classroom activities: choice of task and persistence of task. Previous research mostly used quantitative methods to understand students’ general motivation, without taking contextual factors into consideration. To fill in this gap, the present study examined the influence of changing contexts on students’ motivational beliefs in a Chinese language classroom, and how those changes in motivational beliefs shaped their motivational behaviours in class activities. An ethnographic multiple-case study approach was adopted, and six adult learners were chosen from a Chinese language course in a Hong Kong university. On-going semi-structured interviews, class observations, stimulated recall and document reviews were conducted to understand student development across time. Findings show that the more proficient students were showing relatively stable motivational beliefs as well as behaviours throughout the foreign language course. In contrast, the less proficient students were demonstrating obvious changes in their motivational beliefs and hence behaviours, due to the different contexts of non-exam and high-stake exam. The study suggested students’ learning motivation in class was context-dependent, and could fluctuate substantially on a weekly basis. Those dynamic within-course changes at different learning stages and the reasons shaping the changes could give pedagogical insights to the teacher with adult learners.